Isolamento e identificação de leveduras fermentadoras de D-xilose e produtoras de xilanases associadas à madeira em decomposição de dois ecossistemas de Mata Atlântica - Camila Gontijo de Morais (2013)
Due to the depletion of oil reserves and environmental issues related to its use, it is necessary to search for alternative and renewable sources of energy. The lignocellulosic ethanol is interesting because it is manufactured from lignocellulosic biomass, an abundant and cheap material. The obstacles for lignocellulosic ethanol production include the absence of a micro-organism capable of producing the enzymes required for the degradation of hemicellulose and yeasts capable of fermenting D-xylose. The aim of this study was to isolate yeasts that assimilate D-xylose and xylan present in decaying wood as sole carbon source, and to test them for their ability to ferment D-xylose and to produce extracellular xylanases. Thirty hundred and twenty-six yeasts were isolated, and in the screening tests 28 (8.58%) isolates produced xylanases and 49 (15.03%) fermented D-xylose producing ethanol. Most xylanase-producing yeast isolates was identified as Sugiyamaella xylanicolla, a new species identified in this work. Most yeast fermenting D-xylose was identified as Scheffersomyces (Candida) queiroziae and S. stipitis. Furthermore, we isolated 18 possible new species, three of which produced xylanases and three fermented D-xylose. The isolation of new yeast species that produce enzymes and ferment D-xylose from the Atlantic Rain Forest sites studied, shows the potential of of this environment to obtain new microorganisms of interest for the production of lignocellulosic ethanol.